Coherent Detection-Based Optical OFDM, 60 GHz Radio-over-Fiber Link Using Frequency Quadrupling, and Channel and Carrier Phase Estimation - Thool, Sunil N; Chack, Devendra; Kumar, Amitesh (Frontiers in Physics, 2021)
The optical orthogonal frequency division multiplexing (OFDM) is proven to be a most promising technology for the next generation high capacity and ultra-wide bandwidth 5G communication systems. 60 GHz millimeter wave (mm-wave) frequency band is also becoming a most popular upcoming frequency spectrum due to today’s available dense frequency spectrum used for mobile, multimedia and data communication etc. We propose a system comprises of 60 GHz Radio over Fiber (RoF) model using optimized optical frequency quadrupling, coherent detection, channel estimation and carrier phase correction techniques for ultra-wide bandwidth 16-quadrature amplitude modulation (QAM) OFDM baseband signal. The proposed RoF system's outcomes are shown relatively better bit error rate (BER) of 3.1×10-3 to enable successful transmission of 110 Gbps data for more than 105 km optical link comprising of standard single-mode fiber (SSMF). System performance and obtained results shows a potential to fulfill the requirements of 5G and cellular communication system.